Introducing the Speaking Valve: Letter to Editor - Alireza Aghaz (Vesnu Publications, 2020)
Patients with a tracheostomy for any reason usually do not have speech or swallowing. Lack of communication and swallowing problems negatively affect all aspects of the patient's life. By attaching a speaking valve on the tracheostomy tube, patient's speech, swallowing, and cough can be facilitated, and aspiration would reduce. The use of a speaking valve also restores patient's sense of smell and taste, and usually facilitate decannulation process. In developed countries, most physicians and clinicians are familiar with and prescribe speaking valves, but Iranian medical community is still unfamiliar with the speaking valve and its benefits. At present, this tool is not available in Iran for patients and even medical staff, and is not practical. It seems that by conducting clinical studies, advertising, and holding training workshops for clinicians, the level of awareness of medical community and patients about the use of speaking valves and its benefits can be increased.